Synthesis, molecular docking and evaluation of novel sulfonyl hydrazones as anticancer agents and COX-2 inhibitors - KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (SPRINGER, 2020)
In trying to develop new anticancer agents, a series of sulfonylhydrazones were synthesized. All synthesized compounds were checked for identity and purity using elemental analysis, TLC and HPLC and were characterized by their melting points, FT-IR and NMR spectral data. All synthesized compounds were evaluated for their cytotoxic activity against prostate cancer (PC3), breast cancer (MCF-7) and L929 mouse fibroblast cell lines. Among them,N '-[(2-chloro-3-methoxyphenyl)methylidene]-4-methylbenzenesulfonohydrazide(3k)showed the most potent anticancer activity against both cancer cells with good selectivity (IC50 = 1.38 mu M on PC3 with SI = 432.30 and IC50 = 46.09 mu M on MCF-7 with SI = 12.94). Further investigation confirmed that3kdisplayed morphological alterations in PC3 and MCF-7 cells and promoted apoptosis through down-regulation of the Bcl-2 and upregulation of Bax expression. Additionally, compound3kwas identified as the most potent COX-2 inhibitor (91% inhibition) beside lower COX-1 inhibition. Molecular docking of the tested compounds represented important binding modes which may be responsible for their anticancer activity via inhibition of the COX-2 enzyme. Overall, the lead compound3kdeserves further development as a potential anticancer agent. [GRAPHICS] .
Keywords: Anticancer activity; Apoptosis; Cyclooxygenase; Molecular docking; Sulfonylhydrazones; CANCER CELLS; BIOLOGICAL EVALUATION; HYDRAZIDE-HYDRAZONES; CYCLOOXYGENASE-2; APOPTOSIS; EXPRESSION; ABSORPTION; INDUCTION; BINDING; GROWTH